The Influence Of Understanding And Benefits On Interest To Do Transactions With Mobile Banking Case Study At PT. Bank SUMUT KC Shariah Tebing Tinggi - Ramadani, Desi; Wahyuni, Sri Fitri (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine and analyze the effect of understanding and benefit simultaneously on the interest in conducting transactions with Mobile Banking, The location of this research was carried out at PT. Bank SUMUT Sharia Branch Office Tebing Tinggi, Jln. Dr. Sutomo No. 21 Kota Tebing Tinggi, the research time is planned for December 2021 by implementing health protocols. In this study, the population includes PT. Bank SUMUT Syariah KC Tebing Tinggi that uses Mobile Banking services are as many as 350 customer criteria. In this study, partially understanding affects customer interest in using mobile banking as seen from t count t table (4.419 1.991) and the significant level is 0.000 0.05 , In this study partially Benefits affect customer interest in using mobile banking seen from t count t table (6.044 1.991) and the significant level is 0.000 0.05, and the nature of this study simultaneously Understanding and Benefits affect customer interest in using mobile banking because f count f table (77,030 3.12) and the significant level is 0.000 0.05, the R Square value is 0.673 or 67.3%